2021
DOI: 10.1038/s42004-021-00450-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of long-lived cyanide anions in superexcited states

Abstract: The cyanide anion (CN−) has been identified in cometary coma, interstellar medium, planetary atmosphere and circumstellar envelopes, but its origin and abundance are still disputed. An isolated CN− is stabilized in the vibrational states up to ν = 17 of the electronic ground-state 1Σ+, but it is not thought to survive in the electronic or vibrational states above the electron autodetachment threshold, namely, in superexcited states. Here we report the direct observation of long-lived CN− yields of the dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Experiments . In our high-resolution VMI apparatus, a trochoidal electron monochromator is used to reduce the energy spread of thermally emitted electrons. The narrow energy spread can be maintained for the pulsed electron beam (along the y axis), which is essential for obtaining anion velocity images with a high resolution . The anion detector (in the x–y plane) consists of two multichannel plates and a set of delay-line anodes (commercially available from Roentdek, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experiments . In our high-resolution VMI apparatus, a trochoidal electron monochromator is used to reduce the energy spread of thermally emitted electrons. The narrow energy spread can be maintained for the pulsed electron beam (along the y axis), which is essential for obtaining anion velocity images with a high resolution . The anion detector (in the x–y plane) consists of two multichannel plates and a set of delay-line anodes (commercially available from Roentdek, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, more sophisticated computations about the resonant states above 1,3 B 1 of NO 2 – are still needed. What we found here is largely owed to the development of the high-resolution technique for the DEA studies. Perhaps the molecular dissociations in the anionic resonant states are the last unmatured research field of unimolecular reaction, while more and more of their dynamics will be revealed with the high-resolution measurements.…”
mentioning
confidence: 95%
See 3 more Smart Citations